CAN FLAT-RAMP-FLAT FAULT GEOMETRY BE INFERRED FROM FOLD SHAPE?: A COMPARISON OF KINEMATIC AND MECHANICAL FOLDS - Savage H.M.; Cooke M.L. (My University, 2003)
The inference of fault geometry from suprajacent fold shape relies on consistent and verified forward models of fault-cored folds, e.g. suites of models with differing fault boundary conditions demonstrate the range of possible folding. Results of kinematic (fault-parallel flow) and mechanical (boundary element method) models are compared to ascertain differences in the way the two methods simulate flexure associated with slip along flat-ramp-flat geometry. These differences are assessed by systematically altering fault parameters in each model and observing subsequent changes in the suprajacent fold shapes. Differences between the kinematic and mechanical fault-fold relationships highlight the differences between the methods. Additionally, a laboratory fold is simulated to determine which method might best predict fault parameters from fold shape. Although kinematic folds do not fully capture the three-dimensional nature of geologic folds, mechanical models have non-unique fold-fault relationships. Predicting fault geometry from fold shape is best accomplished by a combination of the two methods.
Keywords: FAULT-BEND FOLDING; MECHANICAL MODELS; KINEMATIC MODELS; FAULT GEOMETRY PREDICTION